2020
DOI: 10.21203/rs.3.rs-21922/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neuroinflammation is associated with infiltration of T cells in Lewy body disease and ɑ-synuclein transgenic models.

Abstract: Background: ɑ-synuclein (ɑ-syn) is a presynaptic protein which progressively accumulates in neuronal and non-neuronal cells in neurodegenerative diseases such as Parkinson’s disease (PD), dementia with Lewy bodies (DLB), and multiple system atrophy. Recent evidence suggests that aberrant immune activation may be involved in neurodegeneration in PD/DLB. While previous studies have often focused on the microglial responses, less is known about the role of the peripheral immune system in these disorders.Methods: … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 70 publications
(93 reference statements)
0
3
0
Order By: Relevance
“…T lymphocytes are altered and infiltrate the brain in PD [22][23][24][25][26][27][28][29] and it has been reported that autoreactive T lymphocytes directed against ␣-syn are present in PD patients [30] decades prior to motor PD [31]. Recruitment of CD4 + T cells to the brain occurs in models of a-syn overexpression [32]. In PD models, T cell function has been linked to ␣-syn pathobiology [33][34][35] and to the death of dopamine neurons [8,36].…”
mentioning
confidence: 99%
“…T lymphocytes are altered and infiltrate the brain in PD [22][23][24][25][26][27][28][29] and it has been reported that autoreactive T lymphocytes directed against ␣-syn are present in PD patients [30] decades prior to motor PD [31]. Recruitment of CD4 + T cells to the brain occurs in models of a-syn overexpression [32]. In PD models, T cell function has been linked to ␣-syn pathobiology [33][34][35] and to the death of dopamine neurons [8,36].…”
mentioning
confidence: 99%
“…Numerous studies have demonstrated T cell involvement in the pathophysiology of PD. T cells infiltrate into the brain in different animal models of PD, including 6-hydroxydopamine (6-OHDA)-induced neurodegeneration in mice and rats (Theodore and Maragos, 2015;Ambrosi et al, 2017), the 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) model in mouse (Reynolds et al, 2010;González et al, 2013), human α-synuclein (α-syn)overexpressing transgenic mice (hαSyn, Thy1-SNCA) (Sommer et al, 2016;Iba et al, 2020). Other studies demonstrated that T celldeficient mice were resistant to MPTP-induced neurodegeneration (Benner et al, 2008;Brochard et al, 2009;González et al, 2013).…”
Section: Parkinson's Diseasementioning
confidence: 99%
“…LB pathology was originally found in axons before becoming evident in neuronal soma, called "Lewy neurites" (LN; Koch et al, 2015). LB and LN are composed mainly of aggregated α-synuclein (α-Syn), a protein normally found pre-synaptically (Iba et al, 2020) that misfolds when phosphorylated at serine 129 (pS129; Hirai et al, 2004). Abnormal accumulation of α-Syn triggers the death of dopaminergic neurons in PD (Yasuda et al, 2013).…”
Section: Introductionmentioning
confidence: 99%